2023
DOI: 10.3390/life13020574
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Suitability of a Virtual ‘Pink Warrior’ for Older Breast Cancer Survivors during COVID-19: A Pilot Study

Abstract: The COVID-19 pandemic impacted the conduct of in-person physical activity (PA) interventions among older survivors of BC, who need such interventions to stay active and prevent functional decline. We tested the feasibility of virtually delivering an exergame-based PA intervention to older BC survivors. We enrolled 20 female BC survivors ≥55 years and randomly assigned them to two groups. The intervention group (Pink Warrior 2) received 12 weekly virtual exergame sessions with behavioral coaching, survivorship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…All the other studies [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ] have dealt with the use of DH in the life sciences, which, in addition to bioengineering, touched by all, have examined, from time to time, other categories ( Table 1 ), such as Anatomy [ 8 , 11 ], Bioinformatics [ 14 , 16 ], Cell biology [ 8 , 11 ], Neuroscience [ 8 , 12 , 15 , 17 , 20 ], Physiology [ 9 , 10 , 12 , 13 ], Population biology [ 14 , 16 , 18 , 19 ], and others that are shown in Table 1 .…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…All the other studies [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ] have dealt with the use of DH in the life sciences, which, in addition to bioengineering, touched by all, have examined, from time to time, other categories ( Table 1 ), such as Anatomy [ 8 , 11 ], Bioinformatics [ 14 , 16 ], Cell biology [ 8 , 11 ], Neuroscience [ 8 , 12 , 15 , 17 , 20 ], Physiology [ 9 , 10 , 12 , 13 ], Population biology [ 14 , 16 , 18 , 19 ], and others that are shown in Table 1 .…”
mentioning
confidence: 99%
“…The importance of DH application in the physiological issues related to physical activity was investigated in [ 12 , 13 ], through population surveys. In [ 12 ], the authors tested the feasibility of virtually delivering an exergame-based physical activity intervention to older breast cancer survivors, while the authors of the study reported, in [ 13 ], that they investigated the changes experienced by Austrian therapists when switching to psychotherapy at a distance.…”
mentioning
confidence: 99%
See 3 more Smart Citations